From the History of Names of the Khorazm Province (Eurasian Journal of History, Geography and Economics, 2023)
In this article, the history of the creation of the civilization of the ancient Khorezm region, the history of ancient cities and cultures, their formation and development, is covered. In addition, information is given about the toponyms of Khorezm and its specific features.